INFLUENCE OF TA’AWUN (MUTUAL COOPERATION) IN SUSTAINING CREATIVITY AND INNOVATION AMONG ENTREPRENEURSHIP DEVELOPMENT CENTRES OF UNIVERSITIES IN MALAYSIA - Suhaimi Mhd Sarif; Yusof Ismail (Online Journal of Islamic Management and Finance (OJIMF), 2023)
Creativity and innovation in entrepreneurship contribute to economic growth and employment opportunities. In any economy, policies on social, political, technology, and economics should encourage long-term economic growth. Creative technology entrepreneurship may be used as a feasible alternative to contribute towards the economic growth. Creative technology entrepreneurship provides the ’sustainability’ feature to face continuous uncertainty. In doing so, creative technology entrepreneurship education plays a significant role in providing university students not only with formal training but also hands-on competency to apply creative technology entrepreneurship. The primary objective of this study was to explore the influence of ta’awun (mutual cooperation) in entrepreneurship development centres of universities in sustaining creativity and innovation. The study interviewed policymakers and educators of technology entrepreneurship to investigate the phenomenon. The results of the study showed that ta’awun has been incorporated in the formal tertiary education programme among entrepreneurship development centres to meet the requirements of creativity and innovation. The findings suggest that follow-up studies use a larger size of informants and a greater scope of the study to obtain more robust, comprehensive, and generalizable results.